Analisis Pilihan Konsumen Dalam Mengkonsumsi Beras Organik Di Kabupaten Sragen - Dyah Panuntun Utami (MEDIAGRO, 2011)
This research aims to determine: (1) lexicographic preference of organic and non-organic rice consumption; and (2) factors influence lexicographic preference. Sragen was chosen as location of this research since Sragen is one of organic rice producer in Indonesia.  Descriptive analytic method was applied by implementing purposive sampling to get 126 consumers as respondents in this research. Multinomial logistic model was implemented to determine factors influences of lexicographic preference. Reference category is lexicographic preference of non-organic rice. Result of research of show that influence lexicographic preference in consumption of labeled organic rice and unlabeled organic rice are hedonic price of rice, pesticides residual, and consumer motivation.   Key Words:   Organic Rice, Lexicographic Preference, Consumption